Britain in Europe prospects for change - Milfull, John (Ashgate, 1999)
Stressing the relationship between internal democratization, devolution and regional autonomy; the development towards a democratic and integrated federal Europe; and past interactions between Britain and Europe, - this text considers developments towards "Europeanization" at the grass roots level.